2013
DOI: 10.2522/ptj.20120255
|View full text |Cite
|
Sign up to set email alerts
|

A Higher-Order Analysis Supports Use of the 11-Item Version of the Tampa Scale for Kinesiophobia in People With Neck Pain

Abstract: The TSK-11 can be considered an interval-level measure when used in people with neck pain. It provides potentially important information regarding the nature of neck-related disability. Clinically important difference may not be consistent across the range of the scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…Previous studies had found a significant correlation between kinesiophobia and pain intensity in older persons with LBP [5, 16, 58]. However, our study did not demonstrate similar findings, as we found insignificant correlation between kinesiophobia and pain in older persons with LBP.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Previous studies had found a significant correlation between kinesiophobia and pain intensity in older persons with LBP [5, 16, 58]. However, our study did not demonstrate similar findings, as we found insignificant correlation between kinesiophobia and pain in older persons with LBP.…”
Section: Discussioncontrasting
confidence: 97%
“…The TSK-11 consists of 11 questions that can be divided into two factors which are somatic factors and activity avoidance [57]. The somatic focus would predict perceived disability and activity avoidance focus on actual physical performance, controlling for pain severity [58]. In this study, the Malay® version of TSK-11 was used, with an acceptable level of internal consistency (Cronbach's α of 0.84) and test-retest reliability (ICC = 0.87) [59].…”
Section: Methodsmentioning
confidence: 99%
“…It has shown good psychometric function among a sample of patients with neck pain of various causes and durations. 22 The HADS is a 14-item self-report scale that consists of 2 subscales: depression (HADS Dep ) and anxiety (HADS Anx ). It has proven adequately valid for clinical and research use 19,23 and is a commonly used scale in studies of musculoskeletal pain, including neck pain.…”
Section: Clinical Pressure Pain Threshold Testing In Neck Painmentioning
confidence: 99%
“…It includes 10 domains that are each scored from 0 to 5, for an overall scale range of 0 to 50 where 0 indicates no disability and 50 indicates complete disability. Both the TSK and PCS have been Rasch analyzed by our group and have demonstrated good to excellent congruence with axioms of quantitative measurement in neck pain [26,27]. The HADS has been used extensively in research on people with mechanical neck pain [28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%